Effect of dietary supplementation of calcium, copper and manganese on nutrient utilization, growth, blood biochemical and mineral profile in crossbred heifers - Sharma, Jyoti; Kumar, Anil; Tiwari, D P; MONDAL, B C (The Indian Journal of Animal Sciences, 2011)
Crossbred growing heifers (16) of an average body weight 149 kg and 12–16 month-old were divided into 4 groups of 4 each to study the effect of dietary supplementation of calcium, copper and/ or manganese on nutrients intake, body weight gain, blood biochemical parameters and mineral profile. The heifers of group 1 (control) were supplemented with 60 g feed mixture without calcium, copper and manganese supplementation as top dress, whereas heifers of group 2 were supplemented with 100 g feed (mineral) mixture containing dicalcium phosphate and copper sulphate to supply 11 g Ca and 60 mg Cu /animal / day. The heifers of group 3 were supplemented with 60 g feed (mineral) mixture containing copper sulphate and manganese sulphate to supply 60 mg Cu and 100 mg Mn/animal/day and of group 4 were supplemented with 100 g feed (mineral) mixture containing dicalcium phosphate, copper sulphate and manganese sulphate to supply 11 g Ca, 60 mg Cu and 100 mg Mn/animal/day, respectively. All the heifers were provided concentrate mixture as per requirements along with mixed fodder (green sorghum + green maize + wheat straw). The feeding trial lasted for 100 days. The average daily dry matter and TDN intakes and daily body weight gain were higher in heifers of groups 2 and 4 supplemented with calcium and copper. The digestibility of dry matter, organic matter, crude protein, ether extract and crude fibre was significantly higher in heifers of groups 2, 3 and 4 as compared to control group. The SGPT, SGOT and ALP activities and concentration of total protein, globulin, phosphorus, copper and manganese in blood serum were significantly improved in groups supplemented with minerals but the values were within normal range, whereas cholesterol and glucose concentrations were significantly lower in mineral supplemented groups as compared to control group. The study showed that dietary calcium, phosphorus, copper and manganese supplementation is beneficial for improving the nutrient utilization and weight gain and to maintain the normal blood-biochemical constituents and mineral status in growing crossbred heifers.